2009
DOI: 10.1111/j.1464-410x.2009.08534.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms: lack of change in prevalence and help‐seeking behaviour in two population‐based surveys of women in 1991 and 2007

Abstract: of Gothenburg in 1991Gothenburg in (2911Gothenburg in ) and 2007 were asked to complete similar self-administered postal questionnaires regarding UI and other LUTS. RESULTSThe mean ( SD , range) age of the two groups was 48.1 (20.4, 20-98 ) years in 1991 and 46.2 (20.0, 20-101) years in 2007, respectively. When comparing the two study populations there were no significant differences in the reported prevalence of UI, OAB or nocturia (defined as two or more voids per night) over time. Nocturia according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 28 publications
1
42
1
2
Order By: Relevance
“…Incontinence is probably significantly under-reported due to the embarrassing nature of the problem and the social stigma and taboo that remains, with many people waiting a significant length of time before seeking help (Strickland, 2014, NICE 2015a, Porrett, 2010and Wennberg et al, 2009. Help seeking behaviour is affected by a number of issues including an individuals experience of incontinence (how much it bothers them), a percepotion that incontinence is an inevitable and normal part of ageing, lack of services or a lack of awareness of available services and knowledge of available treatments (Strickland, 2014 andWennberg et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Incontinence is probably significantly under-reported due to the embarrassing nature of the problem and the social stigma and taboo that remains, with many people waiting a significant length of time before seeking help (Strickland, 2014, NICE 2015a, Porrett, 2010and Wennberg et al, 2009. Help seeking behaviour is affected by a number of issues including an individuals experience of incontinence (how much it bothers them), a percepotion that incontinence is an inevitable and normal part of ageing, lack of services or a lack of awareness of available services and knowledge of available treatments (Strickland, 2014 andWennberg et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Urinary incontinence is often considered as a condition inherent to ageing and many affected individuals are unaware of available treatments [2,3]. As a consequence, it may take a long time before people tend to seek medical advice; more than half of the affected individuals never seek treatment [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…17 In a survey involving 2911 postmenopausal women by Wennberg et al documented predominant storage symptoms when compared to filling or incontinence. 18 These authors concluded that better awareness among postmenopausal women along with easy access to health care significantly reduced LUTS. Tai et al analysed the effect of MetS components on LUTS in their study involving 850 type 2 diabetic women.…”
mentioning
confidence: 99%